Thermodynamic properties of the GdTe3 compound - Imamaliyeva, Samira (Physics and Chemistry of Solid State, 2021)
The alloys of the Gd-Te system in the range of compositions > 75 at% Te were studied by the methods of X-ray diffraction (XRD) and electromotive forces (EMF). From the EMF measurements of the concentration cells relative to the GdTe electrode in the 300-450 K temperature range, the partial thermodynamic functions of GdTe in alloys were determined. By combining these data with the corresponding functions of Gd in GdTe, the partial molar functions of gadolinium in GdTe3+Te alloys, and standard thermodynamic functions of formation and standard entropy of the GdTe3 compound were calculated. The obtained results were compared with the literature data.